{The effect of using Thomas and Robinson's strategy (PQ4R) on the achievement and development of reflective thinking skills among students of the College of Education for Humanities - Dr. Waleed Abdel Rahman Ismail Al-Obaedi (Journal of College of Education, 2024)
The current research aims to know the effect of using the Thomas and Robinson strategy (PQ4R) in the achievement and development of reflective thinking skills among students of the College of Education for Humanities The research sample consisted of 68 male and female students from the first stage of the Department of Qur’anic Sciences and Islamic Education at the College of Education for Humanities / University of Wasit Distributed into two sections, Section A included (33) male and female students who represented the experimental group that studied the Qur’anic Sciences subject using the Thomas and Robinson strategy (PQ4R While Section B included (35) male and female students, representing the control group, which studied the Qur’anic Sciences subject in the usual way To achieve the objectives of the study, two tests were prepared: one was an achievement test in the subject of Quranic Sciences and the other was a test of reflective thinking skills The results showed statistically significant differences attributed to the teaching method in the two tests, and the differences were in favor of the experimental group In light of the results, the study recommended including Thomas and Robinson’s (PQ4R) strategy in teaching and learning Islamic sciences
Keywords: Thomas and Robinson PQ4R Strategy, Achievement, Reflective Thinking